Anthony Collins o wolnej woli, wolności i konieczności - Spryszak, Przemysław (Studia z Historii Filozofii, 2024)
Abstract: The paper discusses a stance on free will, liberty and necessity taken by the English philosopher and freethinker Anthony Collins (1676–1729) in the following anonymously published essays: An Essay Concerning the Use of Reason in Propositions the Evidence whereof depends upon Human Testimony (1707), A Philosophical Inquiry Concerning Human Liberty (1717), and, as I assume, in A Dissertation on Liberty and Necessity (1729). Generally speaking, in these works, Collins purported to reconcile the liberty of the man with the necessity with which, as he argued, their acts of will are performed. The paper specifies this position and outlines its philosophical and historical context. It also observes that two objections, most likely unrecognized by Collins, make his conception unsatisfactory. First, Collins downplays the subjective nature of human actions. Secondly, he assumes, implicitly and illegitimately, that, necessarily, unnecessary acts would be (ceteris paribus) performed differently than the necessary ones.